Redefinisi Peran Orang Tua Dalam Pendidikan; Penanaman Sikap Anti Radikalisme Sejak Usia Dini - Pratiwi, Hardiyanti (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Radicalism easily impacts young people who are silence, unemployed, having less social interaction and religion education problem. online media is the most effective dissemination media for radicalism and terrorism. On the other side, industry revolution 4.0 causes the increment of unemployed young people. In education, industry revolution causes the change of learning system from conventional to digital; e-learning. Online learning source has several advantages; however, there are also several negative effects. The more learning online source used, the filter of the negative effects should be increased, otherwise, the increment of unemployed and the high-intensity use of online media will affect the dissemination of radicalism significantly. Education institution could not filter the sources accessed by pupil by oneself. In this case, parents play important role to keep children’s spiritual, moral, emotional and social education good. Unfortunately, a lot of parents no longer realize their role as educator, especially a mother who decides to be a carrier woman. All this time, education is imposed to teacher and education institution, while parents only play a complement role. Parents should be the main educators of their children in order to prevent quick dissemination of radicalism. This article attempts to analyze guidance from the Hadith of prophet Muhammad PBUH for parents so that all aspects of their children’s education based on affection and they are anti-radicalism from the early childhood. Based on that foundation, the children would not be influenced by extremisme and terrorisme on behalf of religion.